Concise Review: Mesenchymal Stem Cells Ameliorate Tissue Injury via Secretion of Tumor Necrosis Factor-α Stimulated Protein/Gene 6 - Zhigang He; Jie Hua; Zhenshun Song (Stem Cells International)
Numerous reports have described therapeutic benefits in various disease models after administration of the adult stem/progenitor cells from bone marrow or other tissues referred to as mesenchymal stem cells/multipotent mesenchymal stromal cells (MSCs). They all showed that one of the important effects of MSCs is to act against excessive inflammatory responses and repair the damaged tissues. The therapeutic benefits of MSCs were initially interpreted by their migration, engraftment, and differentiation into target tissues. However, remarkable anatomical structural repairs and functional improvements were increasingly observed with a small number of or even no MSCs in the injured tissues. This suggests that most beneficial effects are largely due to paracrine secretions or cell-to-cell contacts that have multiple effects involving modulation of inflammatory and immune responses. Currently, the therapeutic benefits of MSCs are in part explained by the cells being activated by signals from injured tissues to express an anti-inflammatory protein, tumor-necrosis-factor-α-induced protein 6. This important mechanism of action has attracted increasing attention, and therefore we conducted this review to summarize the latest research.